2014
DOI: 10.1038/gim.2013.80
|View full text |Cite
|
Sign up to set email alerts
|

Variations in predicted risks in personal genome testing for common complex diseases

Abstract: Purpose The promise of personalized genomics for common complex diseases depends, in part, on the ability to predict genetic risks on the basis of single nucleotide polymorphisms. We examined and compared the methods of three companies (23andMe, deCODEme, and Navigenics) that have offered direct-to-consumer personal genome testing. Methods We simulated genotype data for 100,000 individuals on the basis of published genotype frequencies and predicted disease risks using the methods of the companies. Predictiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 17 publications
1
57
0
Order By: Relevance
“…Many researchers and professional societies have expressed concerns about the unclear predictive ability and clinical utility of the tests; [1][2][3] others showed no evidence of adverse psychological or behavioral consequences. [4][5][6][7][8][9][10] Although the scientific studies conducted so far have indeed shown no evidence of adverse effects, they all had serious limitations that hampered the proper interpretation and generalizability of the findings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers and professional societies have expressed concerns about the unclear predictive ability and clinical utility of the tests; [1][2][3] others showed no evidence of adverse psychological or behavioral consequences. [4][5][6][7][8][9][10] Although the scientific studies conducted so far have indeed shown no evidence of adverse effects, they all had serious limitations that hampered the proper interpretation and generalizability of the findings.…”
mentioning
confidence: 99%
“…2 Most people have probably received risk estimates that were only slightly higher (or lower) than the average risk for a disease, and these were not sufficiently alarming to increase anxiety and distress. The findings of such studies can be generalized to other personal genome tests with limited predictive ability but not to tests that yield very informative test results.…”
mentioning
confidence: 99%
“…Although the accuracy of the technology used is considered to be high, there are no agreed standards to which the company can conform for validating hundreds of simultaneous variant calls. There is also controversy about how to evaluate the accuracy of risks estimated using multiple variants or across ethnicities 2,3 . And consumers might not read or fully understand the company's clear statements that its tests identify only the most common genetic variants and cannot substitute for genetic testing ordered by physicians to assess specific indications, such as a family history of cancer.…”
mentioning
confidence: 99%
“…In addition, prostate cancer was one of the diseases included in direct-toconsumer genetic risk assessments for multiple diseases offered by deCODE, Navigenics, and 23andMe. 68 The offer of the all of the deCODE tests and the Navigenics test seems to have since been discontinued. In the United States, 23andMe no longer offers health-related genetic reports 69 ; in Canada and the United Kingdom, reports on over 100 conditions are offered, but prostate cancer is not listed.…”
Section: Discussionmentioning
confidence: 99%